(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Purpose: The world is experiencing extraordinary challenges that are changing extraordinary challenges that are life changing due to the covid-19 pandemic. The research aims to be used as a baseline to develop preventive actions that can be taken by the government.This study was designed as a cross-sectional online survey. Material and Methods: This study as conducted between May and July 2021, with a total of 370 respondents. The link to the online survey questionnaire was distributed through social media platforms and the personal contacts of the research group members. Results: surviving the pandemic, participants were important in consuming nutrients such as supplements of B6 Vitamin C and Vitamin E (p<0.05). In foods to prevent covid there are results that are of interest in yellow, red, and orange fruits and vegetables (23.51%). No difference was seen in physical activity during the pandemic and before the pandemic (p<0.05). Our data shows that the participants maintain physical fitness through sports activities with endurance training 2-3 days per week. Conclusion: This is accompanied by an optimal increase in body immunity, so as to avoid various kinds of virus attacks that harm the body's condition. The factor of exercise is very big influence so that the body's immunity is always maintained. The body's immunity can work optimally and perfectly because with a healthy lifestyle, nutrition can affect the health of the body not susceptible to disease.